The virtualization of Health Education in times of COVID-19 - Karla Angélica Silva do Nascimento; Deodato Narciso de Oliveira Castro Neto; Julio César Couto Bem Siqueira Telles (Editora da Universidade de Santa Cruz do Sul, 2021)
The study aimed to understand the students' point of view regarding the virtualization of education in the master's degree program classes during COVID-19. This is a case study with a qualitative research approach, using an online questionnaire to identify, into the student's point of view, how virtualized teaching was applied in classes during social distancing. The results show that the use of these resources can significantly contribute to the learning process into the Health area, however, it is essential to invest on training to have a better use of the technologies, since it's not enough that the teacher have the tech resource if a qualified knowledge it's not transmitted to the student.